In the Covid-19 Pandemic, How Well did Zoom Cloud Meeting and Quizizz Media Perform? - Ade Vitarani; Pratiwi Pujiastuti; Anang Sudigdo (STAI Hubbulwathan Duri, 2021)
The purpose of this study was to investigate whether or not the use of Zoom Cloud Meeting and Quiziz media had a substantial impact on students' interest in learning about literature. The participants in this study were 80 students who were enrolled in PGSD UST for the four semesters. This study is a quasi-experimental study that uses a questionnaire approach called the learning interest scale questionnaire to collect data with the help of the Kolmogorov-Smirnov analytical approach and the t-test. Based on the findings of the t-test, it was determined that t = 0.338 and p = 0.563 were significant. When this number was compared to a significance value of 0.05 for the one-score test, the p-value was found to be more than 0.05, indicating a statistically significant difference. Thus, classes taught using Zoom Cloud Meeting and Quizizz media have a higher level of enthusiasm in learning than programs taught using WAG medium (Whatsapp Group).